1976
DOI: 10.1210/jcem-42-6-1104
|View full text |Cite
|
Sign up to set email alerts
|

LH and FSH Responsiveness to Intravenous Gonadotropin-Releasing Hormone (GnRH) in Children with Hypothalamic or Pituitary Disorders: Lack of Effect of Replacement Therapy with Human Growth Hormone

Abstract: To evaluate the diagnostic and prognostic usefulness of the GnRH test, gonadotropin responses to iv GnRH (Parke-Davis) were determined in 82 young patients (2,5 mo.-21 yr.) and 6 normal men. After extensive evaluation, 40 patients (31 boys and 9 girls) were considered "endocrinologically normal." Repeat tests were performed in 17 patients at 6-12 mo. intervals. Nine patients with presumed isolated hGH deficiency and 3 patients with multiple pituitary deficiencies were studied before and at the end of 12 mo. of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our result may have some correlation with a report of decreased LH and FSH responsiveness to GnRH in children with presumed isolated hGH deficiency (20). As their LH and FSH responsive¬ ness to GnRH was not improved by hGH treat¬ ment, the significance of IGF-I in gonadotropin release in puberty stays unsolved at present.…”
Section: Discussionsupporting
confidence: 79%
“…Our result may have some correlation with a report of decreased LH and FSH responsiveness to GnRH in children with presumed isolated hGH deficiency (20). As their LH and FSH responsive¬ ness to GnRH was not improved by hGH treat¬ ment, the significance of IGF-I in gonadotropin release in puberty stays unsolved at present.…”
Section: Discussionsupporting
confidence: 79%
“…Responsiveness to GnRH 2 hr. Patients with gonadal dysgenesis received one or two 0.0125 has been shown to depend on dosage, route, rate, and frequency &kg pulses in addition to the 0.025 &kg pulse because of of administration, age, sex, sexual maturity, stage of menstrual increased sensitivity to GnRH previously noted in this syndrome cycle, and time of day (7)(8)(9)(10)(11)(12)20,21,23). These studies have shown (7,9,21).…”
Section: Methodsmentioning
confidence: 98%
“…Four patients (patients 3 to 6) had bone ages of <I0 years, completk absence of secondary sexual development, and prepuSpeculation bertal responses to standard GnRH testing (2.5 &kg IV) (12). Five patients (patients 4 to 6, 13 and 14) were growth hormone Direct measurement of h~~o~h~s i a l portal plasma concentra-(GH) deficient based on failure to respond to two provocative tions of GnRH in human is impractical.…”
Section: Methodsmentioning
confidence: 99%
“…In these patients, we evaluated the relative LH and FSH (peak LH or FSH/basal LH or FSH) [17]. We also analyzed ΔLH and ΔFSH (peak LH or FSH minus basal LH or FSH) and got the same conclusion as relative LH and FSH (data not shown) [22]. Blood samples were obtained before, and 15, 30, 45, 60, 90, 120 minutes after intravenous administration of insulin, 100 μg LHRH or 250 μg TRH.…”
Section: Fig 1 Selection Criteria Of Patients In This Studymentioning
confidence: 99%